2018
DOI: 10.1097/mcg.0000000000000540
|View full text |Cite
|
Sign up to set email alerts
|

Rifabutin Triple Therapy is Effective in Patients With Multidrug-resistant Strains of Helicobacter pylori

Abstract: There is no current standard for the growing population of patients with multidrug-resistant strains of H. pylori. The 12-day low-dose rifabutin/high-dose proton pump inhibitor regimen is a safe and reliable option for patients infected with triple-resistant strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 18 publications
1
36
1
2
Order By: Relevance
“…We also add to a growing experience that rifabutin‐containing regimens may be effective for resistant HP infections . Studies in the Netherlands, Italy and Germany have demonstrated that rifabutin resistance is rare, and it is overall considered a third or fourth line agent .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We also add to a growing experience that rifabutin‐containing regimens may be effective for resistant HP infections . Studies in the Netherlands, Italy and Germany have demonstrated that rifabutin resistance is rare, and it is overall considered a third or fourth line agent .…”
Section: Discussionmentioning
confidence: 91%
“…15,16 We also add to a growing experience that rifabutin-containing regimens may be effective for resistant HP infections. [17][18][19] Studies in the Netherlands, Italy and Germany have demonstrated that rifabutin resistance is rare, and it is overall considered a third or fourth line agent. 1,3,20 Rifabutin based therapies are not without side effects, however, as a reversible myelotoxicity has been described, though its reversibility and lack of association with increased infections is notable.…”
Section: Discussionmentioning
confidence: 99%
“…Less impressive results were found in a 12‐patient cohort in Korea in whom only 50% achieved eradication although this study was significantly skewed by the fact that some patients received therapy for 7 days and others 14 days . In a large study from Italy looking at 254 patients harboring triple‐resistant (clarithromycin, metronidazole, levofloxacin) strains 82.9% of the patients were cured with a rifabutin‐based triple therapy …”
Section: Rifabutinmentioning
confidence: 89%
“…This negative change in RFB efficacy could be related to multiple failed eradication attempts, although the exact mechanisms are not known. 10 The most prominent side effect has been reported as myelotoxicity which occurs rarely due to high dose and long-term consumption of RFB. 3 Similarly, in an Australian study on 67 patients, eradication rate of RFB-based triple therapy was found as 95% after one previous failure and 68% after more than one previous failure.…”
Section: Re Sultsmentioning
confidence: 99%
“…9 According to reports, a considerable number of patients who are not cured with first-or second-line treatment strategies might harbor MDR H. pylori, a challenging situation for clinicians. 10 Furthermore, recent reports show that H. pylori isolates from different groups of patients, for example, from different geographical regions, might have different patterns of antibiotic resistance. 10 Furthermore, recent reports show that H. pylori isolates from different groups of patients, for example, from different geographical regions, might have different patterns of antibiotic resistance.…”
mentioning
confidence: 99%